Does early family risk and current quality of care predict indiscriminate social behavior in institutionalized Portuguese children? - Soares, I.; Belsky, J.; Oliveira, P.; Silva, J.; Marques, S.; Baptista, J.; Martins, C. (Attachment and Human Development, 2014)
The current study extends research on the effects of institutionalization, most notably by evaluating the influence of proximal relationship processes over and above prenatal and pre-institutional family experiences. By focusing on current quality of institutional care and the child’s early family background, it examines the influence of variations in the institutionalization experience on displays of indiscriminate social behavior , after taking into account potentially confounding pre-admission experiences. Seventy-four Portuguese children (11-30 months) placed in 17 residential institutions and their primary caregivers participated in the study. Children’s displays of indiscriminate social behavior were assessed based on an observational measure and a semi-structured interview administered to the child’s caregiver. Data on children’s physical and mental development were also collected. Three contextual-risk composites of early family behavior - prenatal, family relational, and emotional-neglect - were created. The quality of institutional care was examined in terms of structural, relational characteristics, and, additionally, of the quality of child-caregiver relationship. Current quality of care experienced in the institution, operationalized in terms of the absence (vs. presence) of a preferred caregiver, predicted indiscriminate social behavior over and above prenatal and family risk conditions that preceded the child’s institutionalization.